Faecal tritium excretion after intravenous administration of 3H-25-hydroxyvitamin D3 in control subjects and in patients with malabsorption. Issue 4 (April 1982) - Compston, J E; Merrett, A L; Ledger, J E; Creamer, B
Abstract : Faecal tritium excretion after intravenous 3H-25-hydroxyvitamin D3 administration was measured in three control subjects and in six patients with small intestine resection or bypass. The mean daily faecal tritium excretion over four to six days ranged from 0.8-1.6% of the injected dose in the controls (mean 1.2) and 0.9-6.8% in the patients (mean 3.7). There was a significant positive correlation between stool volume and the mean daily faecal tritium excretion. No correlation was found between the faecal tritium excretion and the plasma 25-hydroxyvitamin D concentration. Between 2.5 and 19.0% of faecal radioactivity eluted as 3H-25-hydroxyvitamin D3 on silicic acid chromatography. We conclude that faecal loss of endogenous 25-hydroxyvitamin D may be increased after small intestinal resection or bypass. Although the amount lost by this route is relatively small, it may contribute to the development of vitamin D deficiency in patients with malabsorption when endogenous vitamin D3 synthesis is also reduced.